Treatment of Angle Class I Malocclusion Type I and III Using Removable Orthodontic Appliances: Case Report - Leonardo Jaya Setiadi Tanumiharja; Ken Edinata; Yohanes Yoppy Purnomo; Marvin Jaya Setiadi Tanumiharja (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Malocclusion is a dental and oral health problem that adolescents often experience. According to the World Health Organization (WHO), malocclusion is the third most common dental health problem after dental caries and periodontal disease. Malocclusion can cause several problems related to the face, including impaired facial aesthetics and dental issues such as difficulty moving the jaw, temporomandibular disorders, and problems with mastication, swallowing, and speaking. Malocclusion can appear in various forms, the most common being anterior teeth crowding, a condition reported by many patients seeking orthodontic treatment. Removable orthodontic appliances are a safe, easy, and aesthetically acceptable treatment alternative for mild crowding cases. This case report discusses the management of orthodontic treatment in the late mixed dentition period in a male patient with class I type I and type III malocclusion using a removable orthodontic appliance. A 13-year-old male patient came to RSGM Maranatha with complaints of crooked and crowded upper and lower front teeth, which made him insecure when smiling. The patient had never used a fixed or removable orthodontic appliance before. The patient reported no problems with chewing or speaking. There have been changes in the arrangement of the patient's maxillary teeth, but the resulting changes in the mandibular teeth have not been significant. Keywords: Class I Malocclusion, Anterior Crowding, Anterior Crossbite.